Coaching : what really works - Rogers, Jenny (New Delhi Sage, 2021)
This is your essential companion to being a coach. Author Jenny Rogers distills her decades of experience to guide you through the challenges and pitfalls, joys and rewards, and dos and don$1 (Bts of coaching. Whether you are a qualified coach many years into practice, or a trainee moving into your first placement, the book provides a treasure trove of practical strategies and skills, theories and concepts that will enhance your practice. It captures what it takes to be a successful coach, and will support and inspire you to become a more confident, self-reflective practitioner. s
Keywords: Personal coaching